Hajj Fund Polemic (Between Subsidies and Istitha'ah) - Siti Ropiah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research is aimed at demonstrating that an understanding of Istitha'ah in Islam is linked to subsidies carried out by the ministry of religious affairs (BPKH), in order that the performance of the hajj should be sharia. As a result of the increased